PENGEMBANGAN MODEL PENILAIAN BERBASIS TAKSONOMI SOLO PADA KONSEP PEMBAGIAN PECAHAN SEKOLAH DASAR - MARYANTI, Yanti (2014)
This study emerges as a result of teachers' weak attention towards student evaluation process. Teachers nowadays tend to assess students quantitatively. However, students with high score cannot be meant to defeat those whose score are lower quantitatively. Study towards student respond on questions is rarely conducted since answers key are available. As a result, no matter how the test is made, students are still assessed based on true or false while neglecting the analysis of basis used to determine this true or false is. As thisweak of attention nor lock of attempts for improvement from related parties, consequently, students tend to stay at the same tier of thinking. Based on that problem background, writer arranges and develops assessment model with SOLO taxonomy base for fraction distribution concept. This study is conducted at elementary school of Nagarawangi 1 and 3. Research subject is students at 5th grade and math teachers in both schools. Method used is design research model reeves. This paper is constructed as follow. First, it identifies and analysis problem background. Second, it develops prototype solution. Third, it in continues the process to test and fix model design and also as reflection for generating design principle. Model design is implemented in one of the school by using responds that have been made through trial and error in the school other than research subject. The first implementation result is a vary responds. The highest percentage portion is 51,43% at level of pre-structural. 44,28% at level of uni-structural and only 4,29% at level of multy-structural. The second implementation result, the highest percentage portion is 45,83% at level of uni-structural. 24,17% at level of pre-structural, 20,83% at level of extended abstract and 9,17% at level of multy-structural. Keywords: Assessment, SOLO Taxonomy, fraction distribution